HUBUNGAN PENGETAHUAN, SIKAP DAN MOTIVASI TERHADAP PERILAKU MENJAGA HIGIENE VAGINA SAAT MENSTRUASI PADA REMAJA PUTRI - Alfiyah Zahra Ulya; Gadis Meinar Sari; Wahyul Anis (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2022)
Background: Lack of behavior to maintain vaginal hygiene during menstruation in adolescent girls, often causes harm to the reproductive organs, such as pruritus vulvae, and even reproductive tract infections (ISR). The purpose of this study was to describe and analyze the relationship of knowledge, attitude and motivation to the behavior of maintaining vaginal hygiene during menstruation in adolescent girls. Methods: The study was conducted at SMP Negeri 45 Surabaya using a quantitative design with a cross-sectional approach. The number of research samples was 114 respondents who met the inclusion criteria. Collecting data using a questionnaire and analyzed by Chi-square test. Results: The results of the Chi-Square analysis showed that there was a relationship between knowledge and behavior (p = 0.001) with an OR value of 4.916, which means that knowledge has a four times greater chance of influencing vaginal hygiene behavior during menstruation. There is a relationship between attitudes towards behavior (p < 0.001) with an OR value of 12.632, which means that attitudes have a 12 times greater influence in influencing vaginal hygiene behavior during menstruation in adolescent girls. While the relationship between motivation and behavior (p = 0.492) vaginal hygiene during menstruation in adolescent girls did not have a significant relationship. Conclusion: Vaginal hygiene behavior during menstruation in adolescent girls is influenced by knowledge and attitudes. The behavior of maintaining bad vaginal hygiene during menstruation can cause germs to easily enter and cause reproductive infections that have a bad impact in the future. Keywords: knowledge, attitude, motivation, behavior in adolescence menstruation